RUMAH TAK LAYAK HUNI DALAM KARYA LUKIS POST-IMPRESSIONISME - MISDA WENI, Yasrul Sami B, S.Sn., M.Sn. (Universitas Negeri Padang, 2019)
This Final Project aims to visualize uninhabitable homes in the formo of post impressionist paintings. As well as showing the importance of the role of the government in overcoming poverty in the middle and lower classes of society in order to alleviate the burden of their suffering and get a better life. The method in making this work, through several stages, namely: Preparation, Elaboration, Synthesis, Realist concepts and Resolutions are then exhibited. The works presented are depictions of uninhabitable homes in the lives of the poor, ten titles are as follows: My neighbor's house, Neglected, Disadvantaged, Shack, Old house, Ground floor house, Their suffering, Life Lantern ?, Their porch and Palace.Keywords: Houses, Uninhabitable, Painting, Post-Impressionism.